2008
DOI: 10.2478/10004-1254-59-2008-1918
|View full text |Cite
|
Sign up to set email alerts
|

How Volatile Organic Compounds Affect Free Radical and Antioxidant Enzyme Activity in Textile Workers

Abstract: Various effects of exposure to volatile organic compounds (VOC) have recently become an important issue because of their widespread use in industry. The aim of this study was to determine the effect of volatile organic solvents commonly used in textile paint industry on free radical levels and the antioxidant enzyme system in textile workers. The study included twenty exposed workers and twenty controls. Blood samples were taken after an overnight fast of 10 to 12 hours. Malondialdehyde (MDA) and total antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…Despite the fact that some of these compounds are not considered carcinogenic by the International Agency for Research on Cancer (IARC), a mixture of them or some individual metals can contribute to increase the risk of cancer [4,5], neurological issues [6], hearing loss [7], and hepatic [8] and respiratory [9] diseases. The exact mechanism of such damages is not fully understood, but it is known that occupational exposure to organic solvents [3,[10][11][12] and some metals [13][14][15] can induce oxidative stress and DNA damages. Nonetheless, the occupational exposure to paints is poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that some of these compounds are not considered carcinogenic by the International Agency for Research on Cancer (IARC), a mixture of them or some individual metals can contribute to increase the risk of cancer [4,5], neurological issues [6], hearing loss [7], and hepatic [8] and respiratory [9] diseases. The exact mechanism of such damages is not fully understood, but it is known that occupational exposure to organic solvents [3,[10][11][12] and some metals [13][14][15] can induce oxidative stress and DNA damages. Nonetheless, the occupational exposure to paints is poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Also, results of the present study are comparable to that reported by Tekriwal and Parmar [2012] were included. In addition, Bayil et al [2008] reported that, the age of cases was 31.75±2.12 compared to 31.35±3.12 in controls with no significant difference. Finally, results of the present study are comparable to those reported by Shousha et al [2008] who reported that, there is no significant difference between the two groups [cases and controls; exposed and nonexposed to cotton mill] according to their age.…”
Section: Resultsmentioning
confidence: 92%
“…The long-term occupational exposure to organic solvents causes increased MDA levels (Bayil et al, 2008). A preliminary study conducted on a group of workers from a paint and lacquer industry occupationally exposed to styrene, ethylene glycol, toluene, p-xylene, and their mixture showed a statistically elevated concentration of the two main products of LPO, MDA, and 4-hydroxynonenal in plasma, compared to the values found for nonexposed controls (Długosz and Sawicka, 1998).…”
Section: Occupational Exposure To Paintsmentioning
confidence: 96%
“…Exposure to toluene and xylene can be detected in urine by high levels of hippuric acid (HA) and 3-methylhippuric acid (3mHA), respectively, whereas both mandelic (MA) and phenylglyoxylic acids (PGA) are eliminated in urine after exposure to styrene, although MA urinary excretion is also related to exposures to ethylbenzene (ACGIH, 2009). The toxic effect of some organic solvents is connected to the formation of free radicals and ROS during their biotransformation (Bayil et al, 2008), which end up increasing LPO and, consequently, damaging biological membranes (Halifeogclu et al, 2000;Bayil et al, 2008).…”
Section: Research Articlementioning
confidence: 99%